2012
DOI: 10.1029/2011gb004241
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term C accumulation and total C stocks in boreal lakes in northern Québec

Abstract: [1] Here we assess total sediment organic C stocks and long-term C accumulation rates in 13 boreal lakes in northern Québec spanning a wide range of morphometric shapes. The lake basins were mapped using a sub-bottom profiler to obtain total sediment volume, which we combined with organic carbon profiles from Holocene cores to obtain total C mass. The estimated long-term areal C accumulation rates averaged 3.8 g C m À2 yr À1 , lower than previous reports for other boreal and temperate regions. The difference r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
102
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(114 citation statements)
references
References 83 publications
9
102
3
Order By: Relevance
“…10 km 2 ). Similarly, Ferland et al (2012) observed the greatest areal carbon stocks and accumulation rates in the sediments of lake size class 0.1-1 km 2 in 13 boreal lakes in James Bay region in northern Quebec, Canada. In our study region the emission to accumulation ratio (E : A) was lower in the three small and intermediate-sized lakes (Valkea-Kotinen, Alinen Rautjä rvi, and Ekojä rvi, E : A 10-17) than in the two large lakes (Kuohijä rvi and Kukkia, E : A 32-44, Einola et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…10 km 2 ). Similarly, Ferland et al (2012) observed the greatest areal carbon stocks and accumulation rates in the sediments of lake size class 0.1-1 km 2 in 13 boreal lakes in James Bay region in northern Quebec, Canada. In our study region the emission to accumulation ratio (E : A) was lower in the three small and intermediate-sized lakes (Valkea-Kotinen, Alinen Rautjä rvi, and Ekojä rvi, E : A 10-17) than in the two large lakes (Kuohijä rvi and Kukkia, E : A 32-44, Einola et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The water–sediment interface was collected using a Kajak–Brinkhurst gravity corer, except for Lake Marie‐Eve [named L‐40 in Ferland et al . ()]. Sedimentary sequences from the five southernmost lakes have already been published (Carcaillet et al .…”
Section: Methodsmentioning
confidence: 99%
“…Tranvik et al (2009) project that carbon burial in polar lakes will decrease whereas carbon burial in boreal lakes will increase. This review, however, points out that other factors such as permafrost type (yedoma vs. non-yedoma; Walter or lake shape (small and deep vs. large and shallow; Ferland et al, 2012) strongly affect burial efficiencies and may overrule the distinction between boreal and polar regions. More research is needed to shed light on these processes.…”
Section: Lake Carbon Burialmentioning
confidence: 99%